2017
DOI: 10.1111/birt.12324
|View full text |Cite
|
Sign up to set email alerts
|

Mode of birth and postnatal health‐related quality of life after one previous cesarean in three European countries

Abstract: In women with low-risk factors, repeat cesareans result in a poorer HRQoL compared with vaginal birth. When there are no contraindications for vaginal birth, women with a history of one previous cesarean should be encouraged to give birth vaginally rather than have an elective repeat cesarean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
3
23
0
3
Order By: Relevance
“…Similar to Prick et al [27], newborn hospitalization and the mother being readmitted to hospital after being discharged, which falls in line with Fobelets et al [26], and the mother being admitted to an ICU, which agrees with Pia et al [24], were identified in our results as determining factors of worse postpartum QoL. The outcomes reported by Seppänen et al [25] informed that the QoL of the women admitted to an ICU at six months postpartum tended to be similar scores to those given by the general population.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to Prick et al [27], newborn hospitalization and the mother being readmitted to hospital after being discharged, which falls in line with Fobelets et al [26], and the mother being admitted to an ICU, which agrees with Pia et al [24], were identified in our results as determining factors of worse postpartum QoL. The outcomes reported by Seppänen et al [25] informed that the QoL of the women admitted to an ICU at six months postpartum tended to be similar scores to those given by the general population.…”
Section: Discussionsupporting
confidence: 84%
“…Having a poor QoL before pregnancy due to factors unrelated to the pregnancy, birth and postpartum process was also identified as a predisposing factor for low postpartum QoL scores, which coincides with Fobelet et al [26]. The women with a low QoL before being pregnant, for non-related to pregnancy reasons, birth and postpartum period, could be affected by this process because it is a stressful situation [20] that could affect negatively to further worsen or aggravate their QoL.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the evidence has shown that VBAC is associated with less maternal morbidity, fewer complications in future pregnancies, smaller overall cesarean delivery rates, and improved postnatal health-related quality of life at the population level than elective repeat cesareans [ 2 – 6 ]. Thus, spontaneous vaginal births and CD rate reductions have been advocated, along with prevention of VBAC complications [ 7 ] to improve pregnancy outcomes. This study evaluated the risks associated with trial of labor after cesarean (TOLAC) to establish a VBAC antepartum scoring model that can identify VBAC candidates among women with a previous low transverse CD.…”
Section: Introductionmentioning
confidence: 99%
“…Ülkemizde, yüksek sezaryen doğum oranları, önemli bir sağlık sorunudur. Sezaryen doğumun anne-bebek sağlığına olan kısa süreli etkileri ile ilgili önemli kanıtlar bulunmaktadır (3,5,6). Ancak sezaryen doğumların uzun süreli etkileri ile ilgili daha fazla çalışmaya gereksinim bulunmaktadır.…”
Section: Introductionunclassified